Induksi Ekspresi Gen Sitokin/Kemokin pada Sel Makrofag Manusia yang Dipapar Virus Dengue Isolat Indonesia - Siti Warnasih (IPB University, 2014)
Dengue is one of the world's most important arbovirus disease. Dengue pathogenesis has not been yet fully understood. It has been reported that there is involvement of the host immune factors and viral factors. Several studies have shown that concentrations of cytokines/chemokines on blood are significantly increased during infection and viral factors are also involved in disease severity. Therefore, characterization of host gene expression profiles in response to dengue virus infection of different serotypes could provide input for understanding the pathogenesis of dengue. The purpose of this research was to determine expression profiles of the genes (mRNA) of cytokines/chemokines as immune response that are released by monocyte derived macrophages (MDM) cells (host gene) exposed dengue viruses. Four dengue serotypes of Indonesia isolate were used in this study. Peripheral Blood Mononuclear Cells (PBMCs) were isolated from blood cells of healthy donors by Ficoll gradient centrifugation techniques and then differentiated into MDM cells. Quantitative real time RT-PCR was used to quantify expression levels of cytokine/chemokine-encoding genes from MDM cells infected dengue. Four cytokine/chemokine-encoding genes i.e IP-10, MCP-1, IL-10, and MIP-1β known involved in dengue pathogenesis. Measurement of the expression levels of cytokines/ chemokines showed that the dengue virus of serotypes DENV-1 and DENV-3 caused an increase in the expression of genes encoding cytokine IL-10 and chemokine IP-10 is higher than other serotypes. Further research is needed to better determine the pathogenesis of dengue disease.